Legal Regulation of Value Added Tax Payers in Ukraine - КАSIANENKO, Liubov M.; ATAMANCHUK, Nataliа I.; SLASTONENKO, Oksana O.; SHOLKOVA, Tetiana B.; FOMENKO, Yuliia O. (Journal of Advanced Research in Law and Economics, 2019)
Relevance of the subject matter lies in the fact that for Ukraine the issue of legal regulation of value added tax is of pressing and fundamental importance, since its strategic role is dictated by an obligatory condition for Ukraine's accession to the European Union. Furthermore, it is the value added tax that has a powerful tax potential and an important role in the fiscal policy of our country. In this regard, this paper aims to identify and reveal the main problems of legal regulation of value added tax payers in Ukraine, exploring foreign practices in this field, including the implementation of ways of reforming domestic legislation. Empirical, analytical and graphical research methods were used to comprehensively consider the features of legal regulation of value added tax payers. The paper presents the provisions of the current tax legislation on value added tax payers, reveals the peculiarities of registration of a person as a value added tax payer, the identified disadvantages and ways to evade tax legislation by payers; substantiates the need to strengthen the liability of taxpayers by introducing corresponding amendments to the Tax Code of Ukraine. The paper may be useful for scientists, practitioners, students and anyone interested in taxation at large, and indirect taxes in particular. As the value added tax payers, who form the category of large taxpayers, play not only a fiscal but also an important socio-economic role, the study of the features of their taxation is therefore important for society as a whole.